A Fatal Case of Neuroblastoma Complicated by Posterior Reversible Encephalopathy with Rapidly Evolving Transplantation-Associated Thrombotic Microangiopathy - Motohiro Matsui; Atsushi Makimoto; Yuya Saito; Mikako Enokizono; Kentaro Matsuoka; Yuki Yuza (MDPI AG, 2023)
Background: Transplantation-associated thrombotic microangiopathy (TA-TMA) is a severe complication of hematopoietic stem cell transplantation and is sometimes fatal. Observations: A 4-year-old, male patient with stage M neuroblastoma (NBL) who had received an allogeneic bone marrow transplantation (BMT) from his sibling five months previously presented with rapidly progressive posterior reversible encephalopathy (PRES) complicated with TA-TMA. Although the patient was transferred to the pediatric intensive care unit, he died within one week after the onset of the latest symptoms. Conclusions: This is the first description of a fatal case of NBL complicated by PRES with rapidly evolving TA-TMA after an allogenic BMT.